# Mathematics

posted by .

The graph of y = 2^x-3 can be obtained by shifting the graph of y= 2^x
a) 3 units to the right
b) 3 units to the left
c) 3 units up
d) 3 units down
e) 2 units to the right and 3 units up

The equation of the graph that is obtained by reflecting the graph of y = 3^-x in the y axis is

a) y =-3^x
b) y=(1/3)^x
c) y= -(1/3)^x
d) y= 3^x
e) x= 3^y

• Mathematics -

(D)

(D)

## Similar Questions

1. ### geometry

I realy need help please!!!! 1-Describe the translation in words: (x, y) (x - 4, y - 9) A)4 units to the left, 9 units down B)4 units to the left, 9 units up C)4 units to the right, 9 units down D)4 units to the right, 9 units up 2-][3-,2.[1,4],[-5,4]2,-3]at …

How can the graph of g(x)=3square root x+3 be obtained from the graph of g(x)= 3 square root x?

How can the graph of g(x)=3square root x+3 be obtained from the graph of g(x)= 3 square root x?

How can the graph of g(x)=3square root x+3 be obtained from the graph of g(x)= 3 square root x?

7. ### Math

Which of the following statements best describes the effect of replacing the graph of y = f(x) with the graph of y = f(x) + 20?
8. ### Algebra 1 Honors

Which of the following statements best describes the effect of replacing the graph of f(x) with the graph of f(x) − 5?
9. ### math

Which of the following statements best describes the effect of replacing the graph of y = f(x) with the graph of y = f(x) − 11?